Repetitive Concussions in Adolescent Athletes – Translating Clinical and Experimental Research into Perspectives on Rehabilitation Strategies - Semple, Bridgette D.; Lee, Sangmi; Sadjadi, Raha; Fritz, Nora; Carlson, Jaclyn; Griep, Carrie; Ho, Vanessa; Jang, Patrice; Lamb, Annick; Popolizio, Beth; Saini, Sonia; Bazarian, Jeffrey J.; et al. (Frontiers in Neurology, 2015)
Sports-related concussions are particularly common during adolescence, a time when even mild brain injuries may disrupt ongoing brain maturation and result in long-term complications. A recent focus on the consequences of repetitive concussions amongst professional athletes has prompted the development of several new experimental models in rodents, as well as the revision of guidelines for best management of sports concussions. Here, we consider the utility of rodent models to understand the functional consequences and pathobiology of concussions in the developing brain, identifying the unique behavioral and pathological signatures of concussive brain injuries. The impact of repetitive concussions on behavioral consequences and injury progression is also addressed. In particular, we focus on the epidemiological, clinical and experimental evidence underlying current recommendations for physical and cognitive rest after concussion, and highlight key areas in which further research is needed. Lastly, we consider how best to promote recovery after injury, recognizing that optimally-timed, activity-based rehabilitative strategies may hold promise for the adolescent athlete who has sustained single or repetitive concussions. The purpose of this review is to inform the clinical research community as it strives to develop and optimize evidence-based guidelines for the concussed adolescent, in terms of both acute and long-term management.